Selected Decisions and Selected Documents of the International Monetary Fund. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This Volume contains decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, as well as selected documents relating to current activities of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet